Relationship between atherogenic indices and abdominal obesity in residents of Trujillo district, Peru - Araujo Anticona, Carmen Yolanda (2021)
Objective. To determine the relationship between atherogenic indices and the presence of abdominal obesity in residents of the district of Trujillo, Peru. Atherogenic indices related to obesity can provide additional information to the risk established by obesity. Methods. The study was a non-experimental, descriptive correlational and cross-sectional design. The sample consisted of 319 adults between the ages of 25 and 65 years who attended four health centers in the city between July and December 2019. To evaluate the atherogenic indices, the lipid fractions of cholesterol, triglycerides, HDL-C and LDL-C were measured using the Mission Cholesterometer®. Regarding the presence of abdominal obesity, the waist circumference indicators established by the Latin American Diabetes Association were used. Results.The statistical analysis used to relate both variables was the chi square test in the SPSS version 25 program. Abdominal obesity was found in 61.1% of the population. As for the atherogenic indexes, these reached a diagnosis of risk in 75.5 % for the TG/HDL-C cholesterol index, 67.4 % for the Castelli index and 56.4 % for the LDL-C/HDL-C cholesterol index. Only a relationship was found between the TG/ HDL-C index and abdominal obesity (p = 0.004). Conclusion. The TG/HDL-C ratio is better associated with abdominal obesity and should be further considered in the probable diagnosis or follow-up of coronary heart disease or insulin resistance in the obese.